Absolute and Comparative Sustainability of Farming Enterprises in Bulgaria - Bachev, H. (Київський національний університет імені Тараса Шевченка, 2017)
Evaluating absolute and comparative sustainability of farming enterprises is among the most topical issues for researchers, farmers, investors, administrators, politicians, interests groups and public at large. Nevertheless, in Bulgaria and most East European countries there are no comprehensive assessments on sustainability level of Bulgarian farms of different juridical type. This article applies a holistic framework and assesses absolute and comparative sustainability major farming structures in Bulgaria – unregistered farms of Natural Persons, Sole Traders, Cooperatives, and Companies. First, method of the study is outlined, and overall characteristics of surveyed farming enterprises presented. After that an assessment is made of integral, governance, economic, social, environmental sustainability of farming structures of different juridical type. Next, structure of farming enterprises with different sustainability levels is analyzed. Finally, conclusion from the study and directions for further research and amelioration of sustainability assessments suggested.

Оцінка абсолютної і порівняльної стійкості сільськогосподарських підприємств є одним із найактуальніших питань для дослідників, фермерів, інвесторів, адміністраторів, політиків, зацікавлених груп і населення загалом. Проте в Болгарії і більшості країн Східної Європи не існує комплексних оцінок рівня стійкості болгарських ферм різного юридичного типу. У статті оцінено абсолютні і порівняльні показники стійкості основних сільськогосподарських структур у Болгарії – незареєстровані ферми фізичних осіб, індивідуальних підприємців, кооперативів та компаній. Викладено метод дослідження і представлені загальні характеристики обстежених сільськогосподарських підприємств. Після цього проведено інтегральну оцінку управління, економічної, соціальної, екологічної стійкості сільськогосподарських споруд різного юридичного типу. Проаналізовано структуру сільськогосподарських підприємств із різними рівнями стійкості. Запропоновано висновок із дослідження і напрями для подальших розвідок і поліпшення оцінок стійкості.
Абсолютна і порівняльна стійкість сільськогосподарських підприємств у Болгарії
Keywords: farm sustainability; governance; economic; social; ecological aspects; Bulgaria; стійкість ферми; управління; економічні; соціальні та екологічні аспекти; Болгарія